Heat transfer performance and prediction of low global warming potential R134a refrigerant alternatives - Morrow, Jordan Alexander (Kansas State University, 2022)
Due to the Kigali amendment, environmental regulations are phasing out high global warming potential (GWP) refrigerants such as R134a. Since many potential alternative refrigerants have flammability and cost concerns, minimizing system charge is critical. The condenser is typically responsible for 50% of the charge of a system; it is vital to have a fundamental understanding of the flow condensation heat transfer performance of low GWP refrigerants such as R513A and R450A. Flow condensation data were extracted from 35 papers and created a database of 5,030 condensation heat transfer coefficient data points. The data points were compared to predicted values from ten condensation correlations and the mean average error (MAE) for each one was calculated: Akers et al. (1959) (MAE=106%), Cavallini et al. (2006) (MAE=30%), Cavallini et al. (2011) (MAE=29%), Kim and Mudawar (2013) (MAE=28%), Macdonald and Garimella (2016) (MAE=61%), Shah (1979) (MAE=39%), Shah (2009) (MAE=32%), Shah (2013) (MAE=38%), Shah (2016) (MAE=26%), and Traviss et al. (1973) (MAE=46%). Many of the refrigerants in the database were not used for developing these correlations. Limited data were available for R513A (i.e., five studies) and R450A (i.e., one study). A vapor compression cycle experimental setup was designed and built to measure heat transfer performance of R134a alternative refrigerants. Experimental heat transfer coefficient data for R513A and R450A in a 0.95 mm diameter, multiport, mini-channel are presented for a range of mass flux (i.e., 200 – 500 kg/m²s) and quality (i.e., 0.2 – 0.8) at a saturation temperature of 40°C. Condensation heat transfer coefficients for R134a, R513A, and R450A increased with increasing mass flux and quality. R513A condensation heat transfer coefficients were 2.6 – 25.6% lower than R134a heat transfer coefficients and pressure drop were 4.5 – 14.0% lower than R134a pressure drop. R450A heat transfer coefficients were 2.4% higher than R134a at high mass flux and quality and up to 11.7% lower than R134a at lower mass fluxes than R134a heat transfer coefficients; R450A pressure drop were comparable to R134a pressure drop (i.e., 5.0% higher to 9.5% lower). A heat transfer coefficient correlation for low GWP (i.e., less than 750) refrigerants was developed using the Buckingham Pi theorem in conjunction with the MATLAB Optimization toolbox. The new correlation was developed using the condensation heat transfer coefficient database and the new experimental data collected from the experimental apparatus. The correlation is developed from a database of 4,110 data points including 11 synthetic refrigerants [i.e., R32, R41, R152a, R161, R450A, R452B, R454C, R455A, R513A, R1234yf, R1234ze(E)] and a range of diameters (i.e., 0.5 – 12.7 mm), saturation temperatures (i.e., 15 – 83°C), mass fluxes (i.e., 50 – 1200 kg/m²s), qualities (i.e., 0.007 – 0.999), pressure ratios (i.e., 0.15 – 0.91), Bond numbers (i.e., 0.454 – 616), liquid Reynolds numbers (i.e., 347 – 80,084), liquid Prandtl numbers (i.e., 1.87 – 5.64), and vapor Weber numbers (i.e., 8.35 – 27,334). The correlation development used 80% of the data points and tested for accuracy with the other 20% of the data points. The new correlation has a MAE of 24.2% for the data used to build the correlation and a MAE of 24.6% for the data used to test the correlation. The consistency of the correlation to predict the build data points and the test data points shows that the correlation effectively predicts the condensation heat transfer coefficients of these low GWP refrigerants.
Keywords: Condensation; Refrigerants; Low global warming potential; Heat transfer; Correlation